Social Exclusion, Epistemic Injustice and Intellectual Self-Trust - Leefmann, Jon (Social Epistemology, 2022)
This commentary offers a coherent reading of the papers presented in the special issue ‘Exclusion, Engagement, and Empathy: Reflections on Public Participation in Medicine and Technology’. Focusing on intellectual self-trust it adds a further perspective on the harmful epistemic consequences of social exclusion for individual agents in healthcare contexts. In addition to some clarifications regarding the concepts of ‘intellectual self-trust’ and ‘social exclusion’ the commentary also examines in what ways empathy, engagement and participatory sense-making could help to avoid threats to intellectual self-trust that arise form being excluded from participation in communicative practices in the context of healthcare<br
Keywords: Social exclusion; hermeneutical injstice; self-trust; patient involvement